Phylogenetic characterization of H5N1 avian influenza viruses isolated in Indonesia from 2003–2007 - Takano, Ryo; Nidom, Chairul A.; Kiso, Maki; Muramoto, Yukiko; Yamada, Shinya; Sakai-Tagawa, Yuko; Macken, Catherine; Kawaoka, Yoshihiro (Virology (New York, N.Y.), 2009)
The wide distribution of H5N1 highly pathogenic avian influenza viruses is a global threat to human health. Indonesia has had the largest number of human infections and fatalities caused by these viruses. To understand the enzootic conditions of the viruses in Indonesia, twenty-four H5N1 viruses isolated from poultry from 2003 to 2007 were phylogenetically characterized. Although previous studies exclusively classified the Indonesian viruses into clades 2.1.1–2.1.3, our phylogenetic analyses showed a new sublineage that did not belong to any of the present clades. In addition, novel reassortant viruses were identified that emerged between this new sublineage and other clades in 2005–2006 on Java Island. H5N1 viruses were introduced from Java Island to Sulawesi, Kalimantan, and Sumatra Island on multiple occasions from 2003–2007, causing the geographical expansion of these viruses in Indonesia. These findings identify Java Island as the epicenter of the Indonesian H5N1 virus expansion.